What can children learn from exposure to visual-graphical representations?. (June 2021) - Vaknin-Nusbaum, Vered; Nevo, Einat
Abstract: This study examined the relative effectiveness of two intervention programs based on joint-interactive storybook reading: one program focused on cultivating awareness and use of visual-graphic representation (VGR), and the second focused on verbal conversations (VC). Both programs were delivered over 12 sessions, to Hebrew-speaking kindergarteners, by their teachers. Language abilities (vocabulary, narrative skills, listening comprehension, phonological and morphological awareness) and emergent literacy knowledge (print concept and letter naming) were examined both before and after the interventions. Additionally, reading motivation was examined, to find out whether children are more motivated to take part in reading activities after participating in one of the programs. Overall, results showed significant improvement in most examined variables in both intervention groups. The VGR group earned better scores in phonemic and morphemic awareness, print concepts and letter-naming than the VC group. However, scores in vocabulary, narrative ability and listening comprehension improved to a similar degree in both intervention groups. Motivation to read increased only among children who participated in the VC intervention program, while in the VGR group it remained unchanged. Possible implications of the findings to educational settings are discussed.